CYBERSECURITY AND THE INTERNET OF THINGS: A LEGAL ASPECT - Філінович, Валерія Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the main goal of this paper is to study the features and essence of the Internet of Things and the legal possibilities of protecting such a system. Research methods: the research was carried out using generally recognized methods of scientific knowledge, such as analytical, comparative-legal, systemic and structural, and others. The results: the author has investigated the concept, essence, characteristics of the Internet of Things, and aspects of cybersecurity related to it, pointed out the problems of protecting users, and provided suggestions for overcoming such problems. Discussion: the discussion in the article is aimed at finding directions to solve the problem of ensuring a sufficient level of cybersecurity in the Internet of Things system and the need to harmonize domestic legislation on the protection of personal data with international standards. The Internet of Things today has become commonplace, a part of our daily life. And the use of its elements often leads to an increase in the risks associated with cybersecurity. The works of such researchers and scientists as G. Frieder, D. Pushman, P. Pritula, P. Barnaghi, F. Carrez, S. Vlasko, and others were devoted to this problem. In this research study, the author wants to uncover the essence and features of the Internet of Things and provide a critical assessment of the related cybersecurity gaps, as well as provide ways to solve this problem. Today, many devices also known as gadgets can connect to the World Wide Web, receiving and sending certain information. This ability makes the device «smart», respectively, it becomes more efficient. As examples of this, it is worth remembering smartwatches, smart home systems, smart cars, and others. Moreover, such a thing (device) itself should not be super-high-tech, it is enough that it can connect to the servers of such a «supercomputer». But with undoubted benefits, the Internet of Things has brought us a large number of negative aspects associated with «attacks» on cybersecurity: the level of increase in attack vectors has expanded. So, each of us can become a victim of cybercriminals by using familiar things.